PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN DASAR KELISTRIKAN DAN ELEKTRONIKA KELAS X TAV DI SMKN 1 PADANG - Nora Mawinda; Zulkifli Naansah; Hanesman Hanesman (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2014)
The problem in this study is the low learning outcomes achieved by students on the subjects of Basic Electrical and Electronics which is below the minimum completeness criteria (KKM) set a school that is 75 This is presumably because they are learning is often used during the learning model is applied directly proven yet effective. The purpose of this research is to reveal how much influence the Jigsaw cooperative learning model to study the results of class X students on subjects TAV Basic Electricity and Electronics. This research is an experimental study with a draft Post-test only control group design. The sample were students of class X TAV at SMK 1 Padang Academic Year 2014 / 2015. Class experiment is treated using Jigsaw Cooperative Learning Model and the control group is a class that uses the direct teaching model. The data is taken from the test results in the form of learning about the objective as many as 31 items. Data were analyzed manually to test for normality, homogeneity testing, and hypothesis testing. The result of the calculation hypothesis at significance level α = 0.05 was found that t count> t table is 3.35> 1.670. The results of these tests give an interpretation that H0 is rejected and H1 is accepted, this means that on average significantly experimental class learning outcomes greater than the average control class learning outcomes.  Key words :   Models of Learning, Jigsaw, Learning Direct, Post-test only control group design, Learning outcomes, Experimental, and Control.